Enhancing Tensile and Cracking Resistance Performance in Additively Manufactured Parts Through Multiobjective Optimization and Pareto Analysis - Kafshgar, Atefeh Rajabi; Aliha, M. r. m.; Choupani, Naghdali (Wiley, 2025)
Relationships between 3D-printing parameters and tensile characteristics (yield and ultimate strengths, elastic modulus, elongation at break, and toughness) and fracture resistance indices (K Ic, G If, and CMOD) of PLA parts were investigated experimentally and statistically. Infill density was the most important parameter for the yield ultimate tensile stress and modulus of elasticity. Raster angle significantly affected the G If, elongation, and toughness. Layer thickness was the most affecting parameter for K Ic changing. Two groups of the best printing settings were found. The best parameters of the first group (K Ic, G If, elongation, and toughness) were infill density of 60%, temperature of 200 degrees C, raster angle of +45/-45, and thickness of 0.2 mm. For the second group (yield and ultimate strengths and modulus), the optimal settings were 60%-220 degrees C-0/90-0.1 mm. Additionally, several biobjective optimization problems of conflicting fracture and tensile properties were solved, and Pareto solutions were obtained simultaneously. A specific printing setting was proposed via weighted summation of all outputs that increased the tensile and fracture indices from 30% to 180% compared to the worst estimations.
Keywords: 3D printing parameters of PLA; design of experiment; multiobjective optimization; Pareto fronts; tensile strength and fracture toughness experiments